Different Rates of Chicken Manure and NPK 15-15-15 Enhanced Performance of Sunflower (Helianthus annuus L.) on Ferruginous Soil - V. I. Abumere; O. A. Dada; A. G. Adebayo; F. R. Kutu; A. O. Togun (International Journal of Agronomy)
Utilization of adequate fertilizer rate enhances soil physical and chemical properties, minimizes soil nutrient imbalance, and promotes better crop growth and development. The study investigated the influence of varying rates of chicken manure and NPK fertilizers as it affected growth, nutrient uptake, seed yield, and oil yield of sunflower on nutrient-limiting soil. Field experiments were carried out during 2014 and 2015 planting seasons for both main and residual studies. There were eight treatments comprising four rates of chicken manure (5, 10, 15, and 20 t·ha−1), three rates of NPK (30, 60, and 90 kg·N·ha−1), and control. The experiment was laid out in a randomized complete block design with three replicates. Growth, yield, dry matter and proximate, nutrient uptake concentration, and oil content were determined following standard procedures. Data were analyzed using ANOVA, and means were compared with the Duncan multiple range test (DMRT) at p≤0.05. Performance of sunflower was superior on the field fertilized with 10 t·ha−1 chicken manure which was comparable to 90 kg·N·ha−1 NPK fertilizer. Sunflower seed yield and oil quality were superior in plots supplied with 10 t·ha−1 chicken manure which was comparable to 60 kg·N·ha−1 NPK. Growth, yield, dry matter, and proximate content were least in the unfertilized plots.